Effect of M-Learning on promoting the awareness of faculty members of the universities of medical sciences of Iran about their employment regulations in 2020 - Gilavand, Abdolreza (Frontiers in Public Health, 2022)
Introduction New technologies enable universities to incorporate innovative teaching-learning strategies into their curricula. Therefore, this research investigates the effect of mobile learning on promoting the awareness of faculty members of the universities of medical sciences of Iran about their employment regulations. Materials and methods The statistical population of this research included all faculty members of Ahvaz Jundishapur University of Medical Sciences in southwestern Iran. One hundred and fourteen people entered the quasi-experimental study through convenience sampling. First, we sent the designed mobile app to them through social networks to install on their phone. We measured their awareness about the app and M-Learning through a researcher-constructed questionnaire. Results M-Learning and App was able to increase the awareness of faculty members, which was significant according to their academic rank and work experience. Faculty members who were professor and instructor, as well as those who had e under 5 years or 11–20 years of experience gained more awareness (P = 0.00). It was not significant in other variables. Ninety eight percent of the faculty members considered the technical capabilities of the designed app appropriate. Ninety seven percentage of the faculty members suggested M-Learning for teaching similar subjects in their profession. Discussion and conclusion The faculty members had a positive attitude toward this designed educational app and M-Learning. Designing similar mobile training apps can improve their professional performance.